Loneliness and disability: A systematic review of loneliness conceptualization and intervention strategies - Gómez-Zúñiga, Beni; Pousada, Modesta; Armayones, Manuel (Frontiers in Psychology, 2023)
Introduction People with disabilities experience loneliness to a greater extent than people without disabilities. To better understand this problem, we have conducted a systematic review of studies that involved disability and loneliness. The aims are to research what loneliness is and to conceptualize and define it in the context of disability, and the intervention strategies that have been developed. Methods The research protocol is based on the PRISMA guidelines. Two hundred and eighty-one papers were screened and 75 reports were assessed for eligibility. Results We have not found whether loneliness in disability is a single construct or a collection of various subtypes. We have found that there are protective factors against loneliness in disabled people, such as having a job or living in an environment without physical barriers. Discussion In terms of the interventions for people with disabilities, the same strategies have been adopted as for the non-disabled: social skills training, enhanced social support, opportunities for interactions, and cognitive training.